The twelve : a novel - Cronin, Justin (Cronin, Justin. Passage trilogy., 2012)
Survivors of a government-induced apocalypse endure their violent and disease-stricken world while protecting their loved ones; while a century into the future, members of a transformed society determinedly search for the original twelve virals.